Political Metaphors in Hittite Diplomatic and Historiographic Texts - Pallavidini, Marta (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
Research topic: In the Hittite historiographic and diplomatic texts some concepts are formulated metaphorically. In particular, we can find metaphors based on expressions of motion; involving body parts; recalling the comparison between a person and an animal; describing the concepts of life and death; concerning the lexicon of the family and relatives. Theoretical approach: These metaphors are to be considered as expressions of a system of thinking, i.e. as conceptual metaphors (Lakoff – Johnson 1980). Research questions: Which metaphors are attested? How are they structured? How do they dependent on context, language, and/or genre? Which metaphors are of Hittite origin? Which functions do they have? Research goals: Identification, classification and description of the metaphors; analysis of their functions; description of the changes in their use in relation to the genre and through time. Method: the Metaphor Identification Procedure (MIP) of the Praggelejaz Group.